Pemerintah Meluncurkan Pengembangan Kurikulum Baru Guna Memulihkan Pembelajaran Di Masa Pandemi Covid-19 - Dwi Luspita Sari; Desty Isnaini; Mustafiyanti Mustafiyanti (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The curriculum is an important foundation in implementing learning activities to achieve a good direction, because it controls the entire learning process starting from planning to assessment. The principle of curriculum development is the educational curriculum as an implication of learning activities for children who have the quality of workforce needed by society, the educational curriculum must be child-oriented. Changes in curriculum development are a way to improve a curriculum, or are defined as a way to create or improve an existing curriculum. This article is a type of library research that discusses the process and principles of curriculum development in education. Next, the author examines the process and principles of curriculum development in education, which includes the meaning of curriculum development, factors that influence curriculum development, and various principles of curriculum development.